Economic Repercussions of the Israel-Iraq Conflict: A Comprehensive Analysis - Almero Barayev (Global Writing Academica Researching & Publishing, 2024)
The Israel-Iraq conflict has led to significant economic consequences for both nations and the broader Middle East region. This study provides a comprehensive analysis of the economic repercussions of the conflict, focusing on direct costs such as military expenditures and infrastructure damage, as well as indirect costs including trade disruptions, investment declines, and long-term economic instability. By examining historical data and economic indicators, this paper elucidates the multifaceted economic impacts of the Israel-Iraq conflict, offering insights into how prolonged conflict can destabilize economies and impede development. The findings highlight the urgent need for policy interventions aimed at mitigating economic damage and fostering stability in conflict-affected regions.